2020
DOI: 10.1038/s41598-020-58278-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Empty Fruit Brunch reinforcement in PolyButylene-Succinate/Modified Tapioca Starch blend for Agricultural Mulch Films

Abstract: In this study, it focused on empty fruit brunch (EFB) fibres reinforcement in polybutylene succinate (PBS) with modified tapioca starch by using hot press technique for the use of agricultural mulch film. Mechanical, morphological and thermal properties were studied. Mechanical analysis showed decreased in values of modulus strength for both tensile and flexural testing for fibres insertion. Higher EFB fibre contents in films resulted lower mechanical properties due to poor fibre wetting from insufficient matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 38 publications
(38 reference statements)
0
22
1
Order By: Relevance
“…On the contrary, there were relatively higher mechanical properties for a 0% EFB specimen (which contained 30 wt% of starch/glycerol with a 2:1 ratio) in a current study, when compared to a previous study, which only gave 16.12 and 21.78 MPa for tensile and flexural strength, respectively, for pure PBS polymer [ 34 ]. The insertion of starch supposedly reduces the composite’s strength performance due to low compatibility [ 6 ].…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…On the contrary, there were relatively higher mechanical properties for a 0% EFB specimen (which contained 30 wt% of starch/glycerol with a 2:1 ratio) in a current study, when compared to a previous study, which only gave 16.12 and 21.78 MPa for tensile and flexural strength, respectively, for pure PBS polymer [ 34 ]. The insertion of starch supposedly reduces the composite’s strength performance due to low compatibility [ 6 ].…”
Section: Resultscontrasting
confidence: 87%
“…This study is a continuation of previous study, which investigated the characterization of high volume contents of EFB fiber reinforced in PBS/tapioca starch composite [ 34 ]. The high volume of fiber reinforcement found deterioration of mechanical properties due to poor interfacial bonding, evidenced from SEM micrograph and this is not accepted by the market, and similar findings were reported that show a lower tensile strength when alkaline treated-sugarcane fibers were inserted without any plasticizers [ 35 ].…”
Section: Introductionmentioning
confidence: 72%
“…Secondly, these PBS oligomers are trans-esterified under vacuum to form a high-molecular-weight polymer. Because of its excellent processability, which originates from its low melting point and controllable melt flow index (MFI), PBS has been applied in eco-plastics such as mulching films, compostable bags, non-woven fabrics and catering tools that can replace non-degradable polymers [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kenaf fiber consists of three main constituents which are cellulose, hemicellulose and lignin. Low thermal stability properties of hemicellulose constituents start to decompose, followed by cellulose and lignin, ranging from 150 to 380 • C according to a previous study [32]. Lignin constituents thermally decomposed at around 280-500 • C and were responsible for char formation (residual) [33].…”
Section: Discussionmentioning
confidence: 87%